Effectiveness of a Business Development Training for Rehabilitation Counselors Who Work With Consumers Who Are Blind or Visually Impaired. (October 2019) - McDonnall, Michele C.; Sui, Zhen
The passage of the Workforce Innovation and Opportunity Act has placed increased emphasis on business engagement for vocational rehabilitation agencies, yet many rehabilitation counselors are not prepared to work with businesses. The primary purpose of this study was to evaluate the initial effectiveness of a business development training for rehabilitation counselors who work with consumers who are blind or visually impaired. A secondary purpose was to report on the sample's pretraining status on variables associated with business development. Participants were 80 counselors and counselor supervisors employed by four separate agencies who completed the 19-h in-person training. Data were collected from participants prior to and immediately following the training. Outcome variables were self-perceived knowledge, skills, and comfort level with business development activities and measured business development knowledge and self-efficacy. Prior to the training, participants recognized the importance of, and a personal need for training in, business development and perceived moderate levels of comfort, knowledge, and skills. Participants demonstrated statistically significant increases on all outcome measures, with effect sizes ranging from medium to large. These results provide support for the effectiveness of the training in improving business development outcomes in the short term. Additional research is needed to evaluate its long-term effectiveness.